Rancang Bangun Aplikasi Pembelian Bahan Produksi Berbasis Web Pada UD Arbain Grafika Surabaya - Sholihah, Maharani Bilqis; Ayuningtyas, Ayuningtyas; Nurcahyawati, Vivine (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
UD Arbain Graphic Surabaya is the printing services of entrepreneurial ventures. The issue that is Production Division is still a difficulty in controlling stock, determine the re-ordering of materials you’ve almost reached the reorder point. Another problem in the process of recording of the purchase note recapitulation not arranged neatly, making owners of difficulty in the payment process and the recording of the purchase to be invalid. The owner of the difficulty in checking the payment of unpaid / debt payments to Supplier, there are several payments made on time the due date it also. Based on the above issues, the required solution is the Application Web-based Production Material Purchases. The application was made may help determine the amount of raw material to back with obvious method i.e reorder point method; can give information materials usage, the notification function can provide raw materials that must be purchased, and give the function notification of payments. Based on the results of the evaluation, the application is able to display a list of purchases that help its Administration and Owner of the logging in the purchase, Production Division can gelp determine the amount of raw material to reorder point method returns, as well as being able to display the purchase notification and payment to help the Administration Division and Owner in giving the warning.Keywords: Purchase, Raw Materials, Reorder Point.